The Effect of Ozone on the Reversibility of Floc Breakage: Suspensions with High Humic Acid Content - ŞAM, SERDAR (TAYLOR & FRANCIS INC, 2010)
The effects of pre-ozonation and humic acid concentration on the formation, breakup and reformation of flocs generated using aluminium sulphate and polyaluminium chloride was investigated using conventional jar test procedure and by continuous optical monitoring. Using a range of different humic acid and ozone concentrations, it was found that increasing either concentration was detrimental to floc formation, leading to reduced turbidity removal. Once ruptured, only limited regrowth of flocs occurred, indicating irreversible floc breakage. The findings showed that the use of pre-ozonation did not provide beneficial results to improve turbidity removal. Nevertheless, improved dissolved organic carbon removal was achievable.
Keywords: Ozone; Humic acid; Dissolved organic carbon; Floc strength; Coagulation; Flocculation; NATURAL ORGANIC-MATTER; DRINKING-WATER TREATMENT; PRE-OZONATION; COAGULATION; REMOVAL; PARTICLES; FLOCCULATION; DENSITY